Characterization of osthenol metabolism in vivo and its pharmacokinetics. (2nd July 2020) - Cho, Piljoung; Choi, Su Min; Kim, Younah; Lee, Doo Hyun; Noh, Yeeun; Kim, Sujeong; Kim, Ju-Hyun; Lee, Taeho; Lee, Sangkyu
Abstract: Osthenol, a prenylated coumarin, is a C8-prenylated derivative of umbelliferone isolated from the root of Angelica koreana and Angelica dahurica, an intermediate and is known as a major metabolite of desmethyl-osthole. The various pharmacological effects of osthenol have been reported. In previous studies, we investigated five hydroxylated metabolites by cytochromes P450 (CYP) and glucuronide conjugates of osthenol by uridine diphosphate-glucuronosyltransferases (UGTs). However, osthenol have very few studies have been reported on its pharmacokinetic (PK) profiling, we reported the PK parameters in mouse of osthenol through this study. After oral (5 and 20 mg/kg) and intravenous (5 mg/kg) administration, the concentration of osthenol in plasma was determined by LC-MS/MS. The quantitative method was validated in terms of linearity, accuracy, and precision. When 5 and 20 mg/kg of osthenol were orally administered, the bioavailability (BA) was found to be very low at 0.43 and 0.02%, respectively. In fact, osthenol was mostly metabolized to a two-Phase II conjugates, a sulfonyl and glucuronyl-osthenol, in the blood, which was determined by LC-HR/MS analysis of the blood sample. Because osthenol is rapidly metabolized to two conjugates by first-pass effect the BA of osthenol is low after oral administration.